Divide y vencerás: distorsión de la Comunicación en Redes y Poder Político - Pérez Oviedo, Wilson (2007)
In a society composed of a dictator and its citizens, what are the determinants of the political equilibrium between these two? What are the conditions for a successful citizens' revolt? What kind of strategies do governments follow to prevent such revolts? The situation of these types of societies can be understood as a game played between a leader, who has to decide the distribution of the aggregate income, and a group of citizens who have the opportunity to revolt 1f they are unhappy with the distribution. Coordinated action by citizens is possible because they form nodes in a communication network. However, communication through the network is distorted, which could preclude the emergence of collective action among citizens. The network structure and the distortion level are determinants of the political equilibrium and wealth distribution. The model explains how the dictator could use propaganda, cooptation, and repression to increase his expected utility. Finally, the model is illustrated by applying it to cases in Nigeria and Zaire/Congo.